The Effect of Individually-Generated, Teacher-Generated, and Cooperatively-Generated Graphic Organizers on Intermediate EFL Students' Vocabulary Knowledge - Mansoureh Mojaverian; Hossein Siahpoosh; Mehran Davaribina (Journal of English Language Pedagogy and Practice, 2022)
Although previous studies have shown the benefits of graphic organizers in improving learners' vocabulary knowledge, scant attention has been paid to the possible differences in the effect of individually-developed, cooperatively-developed, and teacher-developed graphic organizers on intermediate L2 learners' vocabulary knowledge. The present study addressed this topic by examining 80 intermediate language learners. The participants were selected based on convenience sampling procedure and studied English in four classes. The learners in the conventional group received the translation/definition of the lexical items. Those in the teacher-generated were provided with the graphic organizers prepared by their teacher, and the participants in the other two groups made the graphic organizers either individually or cooperatively. The researchers employed Vocabulary Knowledge Scale as the pre-test, immediate post-test, and delayed post-test to examine the participants' vocabulary knowledge. The findings of this study indicated that the mean scores of the control group in the immediate and delayed post-tests were significantly lower than those of all graphic organizer groups. In addition, the cooperatively-generated graphic organizer group was significantly more successful than learner and teacher-generated graphic organizer groups, but there was no difference between the learner and teacher-generated groups.